11x-32=67

Simple and best practice solution for 11x-32=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-32=67 equation:


Simplifying
11x + -32 = 67

Reorder the terms:
-32 + 11x = 67

Solving
-32 + 11x = 67

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '32' to each side of the equation.
-32 + 32 + 11x = 67 + 32

Combine like terms: -32 + 32 = 0
0 + 11x = 67 + 32
11x = 67 + 32

Combine like terms: 67 + 32 = 99
11x = 99

Divide each side by '11'.
x = 9

Simplifying
x = 9

See similar equations:

| M+22=118 | | 2(-4+7x)=30+6x-6 | | 2x^2-8=4x | | 3x^2-47=1 | | -3(n+7)=12 | | 4--2v=10 | | 28x^2-22x+4=0 | | g/10-20=-19 | | x=(6x+8) | | 3318.1008=2*33.24*r^2+2*3.13*r*36.5 | | w^2-6w-22=-25+w^2 | | 10+2k=18 | | 9k+2=13 | | 0=.01x^2+.7x+6.1 | | 3x+31.5=123 | | w/7+43=46 | | 2s-9=3 | | w^2-6w-22=-25w^2 | | 2(-4+7x)=6x-6+30 | | X+20+2x-5=50 | | 2s-1=1 | | 3y-30=2x | | 2(2y+2)+3y=19 | | 2d+6=16 | | -x+10=-x+14 | | x=(7x+6) | | 3f-3=6 | | 36=9+9s | | (-.01x^2)+.7x+6.1=y | | 24(6)+4x=180 | | y=7x+13forx | | x^2+0.25=1.25 |

Equations solver categories